Zaopatrzeniowy czy ubezpieczeniowy charakter rolniczego ubezpieczenia społecznego? - Puślecki, Damian (Wydawnictwo Naukowe UAM, 2015)
The aim of the paper is to answer the question whether, and if yes, to what extent the farmers’ social insurance should maintain its supply character. With this in mind, the prin-ciples underlying farmers’ social insurance, its main functions as well as the principle of its financing taking into account the idea of social solidarity are shown and analysed. It is concluded that the decision to include farmers into the same system of collection of social insurance premiums developed in the transformation period when agriculture found itself in a very difficult situation was of supply nature. From today’s perspective it may be said that the decision was justified and today’s national budget is less burdened and the situation of the insured farmers improved, although it must continue to improve to increase the quality of their welfare. The insured must also participate to a higher degree in the financing of their insurance, which now is also of insurance character. However, farmers in Poland are unable to finance the entire system of agricultural social insurance and its proper implementation; therefore expected results may not be possible to achieve without support from the national budget.

L’obiettivo dell’articolo è di rispondere alla domanda se e in quale misura l’assicurazione sociale per gli agricoltori dovrebbe mantenere il carattere assistenziale. Per questo motivo l’autore rivela l’essenza dell’assicurazione sociale per gli agricoltori e le funzioni di base, prende anche in esame i criteri di finanziamento, tenendo conto dell’idea di soli-darietà sociale. Nelle conclusioni l’autore sostiene che l’applicazione dei contributi uguali per gli agricoltori conseguiva da una difficile situazione in agricoltura nel periodo di trasformazione dell’ordinamento ed era di carattere assistenziale. Al giorno d’oggi la necessità di introdurre la riforma del sistema di riscossione dei contributi deriva non solo dall’attuale aggravio del bilancio in materia, ma soprattuto dall’esigenza di tutelare gli assicurati e di portare ad un continuo innalzamento della qualità delle prestazioni di cui beneficiare. Una maggiore partecipazione da parte degli assicurati al finanziamento dell’assicurazione è dettata dal suo carattere assicurativo. Tenendo conto dell’attuale stato dell’agricoltura polacca, senza poter impegnare i fondi del bilancio, una corretta attuazione degli obiettivi indicati potrebbe rivelarsi difficile da raggiungere.
A supply or insurance nature of agricultural social insurance?
Assistenziale oppure assicurativo – qual è il carattere dell’assicurazione sociale per gli agricoltori?